1990
DOI: 10.1111/j.1365-2362.1990.tb01876.x
|View full text |Cite
|
Sign up to set email alerts
|

Platelet aggregability in humans: contrasting in vivo and in vitro findings during sympatho‐adrenal activation and relationship to serum lipids

Abstract: Platelet aggregability was studied in 18 healthy volunteers during mental stress (a colour word test; CWT) and low- and high-dose adrenaline infusions using an ex vivo technique (filtragometry) and conventional in vitro aggregometry. CWT and high-dose adrenaline (3.4 nmol l-1 in plasma) shortened filtragometry readings, suggesting increased platelet aggregability in vivo. Low-dose adrenaline had no effect despite higher adrenaline levels in plasma (0.9 nmol l-1) than during CWT (0.4 nmol l-1). Platelet sensiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

1992
1992
2011
2011

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(3 citation statements)
references
References 19 publications
0
2
0
1
Order By: Relevance
“…Additionally, many studies report increases in the levels of the platelet activation markers circulating platelet factor 4 (PF4) and beta-thromboglobulin (BTG) among healthy individuals [6,[116][117][118][119][120][121] and among individuals with essential hypertension [122] and with angina pectoris [123]. However, not all studies have reported significant changes in platelet aggregability [124][125][126] and platelet activation markers [123,127,128] in response to acute stress. For example, Wallén and colleagues [123] reported that acute stress did not elicit elevations in these platelet activation markers in elderly healthy volunteers.…”
Section: Platelets and Stressmentioning
confidence: 96%
“…Additionally, many studies report increases in the levels of the platelet activation markers circulating platelet factor 4 (PF4) and beta-thromboglobulin (BTG) among healthy individuals [6,[116][117][118][119][120][121] and among individuals with essential hypertension [122] and with angina pectoris [123]. However, not all studies have reported significant changes in platelet aggregability [124][125][126] and platelet activation markers [123,127,128] in response to acute stress. For example, Wallén and colleagues [123] reported that acute stress did not elicit elevations in these platelet activation markers in elderly healthy volunteers.…”
Section: Platelets and Stressmentioning
confidence: 96%
“…6 Abnormal plasma markers of endothelial damage (von Willebrand factor (vWF)), 7 platelet activation (soluble P-selectin (s-Psel), 8 CD 40 -ligand (CD 40 L)) 9 and thrombogenesis (D-dimer) 10 are recognized in AMI, but their linkage to autonomic tone is untested. Autonomic tone and platelet-induced thrombosis in vitro is linked by α 2 receptor mediation 11,12 and seen in vivo 13 in studies examining mental stress and dynamic exercise. 14,15 The association of sympathetic stimulation to platelet activation is deduced from β 1 -blockade preventing platelet activation and aggregation.…”
Section: Introductionmentioning
confidence: 99%
“…Η άσκηση προκαλεί την έκκριση της επινεφρίνης από το μυελό των επινεφριδίων και αυτή με τη σειρά της επάγει την ενεργοποίηση των αιμοπεταλίων610 . Άλλος ένας διαφορετικός μηχανισμός μπορεί να είναι ο μετασχηματισμός των α2 αδρενεργικών υποδοχέων των αιμοπεταλίων μετά από οξεία άσκηση, η παραγόμενη από την άσκηση επινεφρίνη ενεργοποιεί τους γλυκοπρωτεινικούς προσδέτες ΙΙb/ΙΙΙ του Ινωδογόνου στην επιφάνεια των αιμοπεταλίων παρουσία του ADP που υπάρχει άφθονο από τους συστελλόμενους μύες λόγω της οξείδωσης του ΑΤP για την παραγωγή ενέργειας· το Ινωδογόνο τέλος ενεργοποιεί τα αιμοπετάλια προς το σχηματισμό θρόμβου[610][611][612][613][614] . Η προκαλούμενη απώλεια ύδατος κατά την οξεία και παρατεταμένη άσκηση προκαλεί αυξημένη αιμοσυγκέντρωση.…”
unclassified